Teaching English usage to second language learners in the high school - Caluag, Aida C. 1929- (s.n.], 1965)
This study presents materials on teaching the correct usage and the levels of usage in the fourth year level of high school. Lessons and exercises are included to show how the said teaching may be accomplished. The items on correct usage are classified according to certain categories.